Carbon dioxide tolerability and toxicity in rat and man: A translational study - van der Schrier, Rutger; van Velzen, Monique; Roozekrans, Margot; Sarton, Elise; Olofsen, Erik; Niesters, Marieke; Smulders, Chantal; Dahan, Albert (Frontiers in Toxicology, 2022)
Background: Due the increasing need for storage of carbon dioxide (CO2) more individuals are prone to be exposed to high concentrations of CO2 accidentally released into atmosphere, with deleterious consequences. Methods: We tested the effect of increasing CO2 concentrations in humans (6-12%) and rats (10-50%) at varying inhalation times (10-60 min). In humans, a continuous positive airway pressure helmet was used to deliver the gas mixture to the participants. Unrestrained rats were exposed to CO2 in a transparent chamber. In both species regular arterial blood gas samples were obtained. After the studies, the lungs of the animals were examined for macroscopic and microscopic abnormalities. Results: In humans, CO2 concentrations of 9% inhaled for >10 min, and higher concentrations inhaled for <10 min were poorly or not tolerated due to exhaustion, anxiety, dissociation or acidosis (pH <7.2), despite intact oxygenation. In rats, concentrations of 30% and higher were associated with CO2 narcosis, epilepsy, poor oxygenation and, at 50% CO2, spontaneous death. Lung hemorrhage and edema were observed in the rats at inhaled concentrations of 30% and higher. Conclusions: This study provides essential insight into the occurrence of physiological changes in humans and fatalities in rats after acute exposure to high levels of CO2. Humans exposed to 9% CO2 retain their ability to function coherently for up to 10 min. These data support reconsideration of the current CO2 levels that pose a risk to exposed individuals (< 7.5%) as determined by governmental agencies.